Preparation and Chemical and Physical Characteristics of an Edible Film Based on Native Potato Starch and Nopal Mucilage - Choque Quispe, David (2021)
Edible films prepared from biological materials are being massively used. This study aimed to prepare edible films from native potato starch of the Allcca sipas variety (Solanum tuberosum subsp. Andigena), nopal mucilage (Opuntia ficus indica), and glycerol. Twelve edible films were prepared with starch, mucilage, and glycerin in different proportions by thermosynthesis. It was observed that mucilage and glycerol have a significant direct effect on film solubility and an inverse effect on aw, while the effect of starch is the opposite. The aw ranged from 0.562 to 0.639. The FTIR analysis showed the interaction of the components in the films being considerably influenced by the addition of mucilage. The TGA/DTA analysis reported low thermal stability in the films, retaining water around 100 ◦C, and showing a tendency to lose weight when the content of starch is high, while the opposite occurred with the addition of mucilage; it was also observed that around 310 ◦C, the maximum weight loss was observed between 53.6 and 86.1%. SEM images showed uniform films without cracks. The results are promising and show the possibility of preparing edible films from native potato starch and mucilage.